An experiment in Bible translation as transcultural communication : the translation of [berith] 'covenant' into Lomwe, with a focus on Leviticus 26 - Foster, Stuart Jeremy (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 2005